DAMPAK TEKNIK PEMBANGKITAN PENYADARAN DAN PENCERMATAN TERHADAP KEEFEKTIFAN KALIMAT BAHASA INDONESIA DALAM TULISAN ILMIAH MAHASISWA - Djiwandono, Patrisius Istiarto (Linguistik Indonesia, 2016)
The paper reports a pre-experimental design that aimed to describe the most frequent mistakes in writing effective sentences in academic essays written by university students. The mistakes were classified into five types: sentences without subject, excessively long sentences, run-on sentences, unfinished sentences, and hanging clauses. It also aimed to determine whether two techniques called Consciousness Raising and Noticing techniques could help the subjects reduce the proportion of their ineffective sentences. The ten subjects were instructed to write academic essays before being taught with the two techniques, and later were instructed again to write essays after being taught with the two techniques. The whole treatment spanned a semester, consisting of twelve sessions in the classroom. The result indicated that run-on sentences, hanging clauses, and excessively long sentences were the most frequent mistakes in their essays. Meanwhile, the Consciousness-Raising and Noticing techniques only had a significant impact on the category of excessively long sentences. The subjects made significantly fewer mistakes in this category after the application of the two techniques. Some implications for further research and practical applications are then presented.